The effect of elastic and inelastic scattering on electronic transport in open systems - Kulinowski, Karol; Wołoszyn, Maciej; Radecka, Marta; Spisak, Bartłomiej J. (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this study is to apply the distribution function formalism to the problem of electronic transport in open systems, and to numerically solve the kinetic equation with a dissipation term. This term is modeled within the relaxation time approximation and contains two parts, corresponding to elastic or inelastic processes. The collision operator is approximated as a sum of the semi-classical energy dissipation term and the momentum relaxation term, which randomizes the momentum but does not change the energy.
Keywords: kinetic equation; relaxation time approximation; scattering processes